Linkages and economic development: The case of Brazil reconsidered - Benedict J. Clements; José W. Rossi (Institute for Applied Economic Research (ipea), 2015)
This paper provides mathematically consistent calculations of the forward, backward, and total linkages in the Brazilian economy in 1975. Our results reveal, among other things, that: 1) high linkages cannot be exclusively associated with modern industrial sectors; 2) none of our linkage measures have any consistent relationship with domestic resource cost, our measure of efficiency; 3) there are some doubts on the proposition that Brazilian economic growth has been linkage-intensive; and 4) there are some important differences between "key" sectors from the standpoint of backward and forward linkages.
Keywords: 330